The Influence of Communication, Work Motivation, and Work Environment on Employee Work Performance Studies on Employees of PT. Global Indo Perkasa Prime in Jakarta - Petrus Faldiano Tri Putra Paila; Prayekti (Formosa Journal of Applied Sciences, 2023)
This study aims to determine: 1) the effect of communication on employee work. 2) the influence of work motivation on employee performance 3) the influence of the work environment on employee performance. 4) the effect of communication, work motivation, and work environment on employee performance. The population of this research is 60 employees of PT. Global Indo Perkasa Prime. The number of samples used was 60 employees of PT. Global Indo Perkasa Prime Jakarta. This research is quantitative with a sampling technique using saturated sampling. The data collection technique used was through sending a questionnaire link which was sent online to the respondents. Data were analyzed using linear regression. The results of this study indicate that the communication variable (X1) has a positive and significant effect on employee performance (Y) with a value of <0.05a (5%).